BUTTERFLY FAUNA OF VICINITY OF JAGODINA (SERBIA) (LEPIDOPTERA: HESPERIOIDEA AND PAPILIONOIDEA) (Acta Entomologica Serbica, 2015)
Altogether, 89 butterfly species (Hesperioidea and Papilionoidea) were recorded between 1993-2014 as results of the fieldwork carried out at 19 localities in vicinity of Jagodina: Hesperiidae – 9 species, Papilionidae – 4, Pieridae – 14, Riodinidae – 1 , Lycaenidae – 22, Nymphalidae – 39. According to Red List status of European butterflies (Van Swaay et al., 2010) one species (Phangaris arionLinnaeus, 1758) is threatened (endangered) at the European level, and three species are considered as Near Threatened (Carcharodus flocciferusZeller, 1847, Zerynthia cerisyGodart, 1824 and Hipparchia fagiScopoli, 1763).Especially important are protected species at European level: Zerynthia polyxena (Denis & Schiffermuller, 1775), Lycaena dispar (Haworth, 1802) and Phengaris arion (Linnaeus, 1758). Also Glaucopsyche alexis (Poda, 1761) as target species for PBA of Serbia.According to scale for estimating the utility of potential Prime Butterfly Area (PBAs) (Jakšić, 2008), the Jagodina region with 89 species, of which four target species, estimated as extreme abundance and qualifies for potential PBAs.